HUBUNGAN PERILAKU PERSONAL HYGIENE DENGAN KERACUNAN PESTISIDA MELALUI PENGUKURAN KADAR CHOLINESTERASE DALAM DARAH PADA PETANI DI PEKON SRIKATON KECAMATAN ADILUWIH KABUPATEN PRINGSEWU TAHUN 2017 - Devi Liani Octiara; fitria saftarina (CV. Jasa Sukses Abadi, 2021)
Pesticides are very popular chemicals used to control the development or growth of pests, diseases, and weeds. Farmers are the largest working group in Indonesia to improve optimal agricultural output, farmers apply various technologies, including the use of chemicals. This study aims to analyze the relationship of personal hygiene behavior with pesticide poisoning in the blood of farmers in Pekon Srikaton Adiluwih Pringsewu District. This research used cross sectional research design with sampling technique such as consecutive sampling. The samples of this research are 86 farmers in Pekon Srikaton Adiluwih Pringsewu District. The statistical analysis was calculated using fisher exact test with a significance value a<5%. The statistical test showed that 20 farmers (91,9%) is pesticide poisoning and not pesticide poisoning is 7 farmers (8,1%), 20 farmers has work experiences less than 10 years (23.3%) and 66 farmers (76,7%) more than 10 years work experiences. Fisher test results obtained p value 0.508. There isn't a relationship between work experiences and pesticide poisoning in blood to farmers in Pekon Srikaton Adiluwih Pringsewu District. This study conclude that there isn’t a relationship between work experiences and pesticide poisoning in the blood of farmers in Pekon Srikaton Adiluwih Pringsewu District.